2016
DOI: 10.1182/blood-2015-06-649970
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of the histone deacetylase SIRT6 in DNA damage response of multiple myeloma cells

Abstract: Key Points• SIRT6 is highly expressed in multiple myeloma cells and blocks expression of ERKregulated genes.• Targeting SIRT6 enzymatic activity sensitizes multiple myeloma cells to DNAdamaging agents.Multiple myeloma (MM) is characterized by a highly unstable genome, with aneuploidy observed in nearly all patients. The mechanism causing this karyotypic instability is largely unknown, but recent observations have correlated these abnormalities with dysfunctional DNA damage response. Here, we show that the NAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 54 publications
4
97
0
Order By: Relevance
“…SIRT6 copy number is increased in some hematopoietic cancer cell lines [5]. Moreover, elevated SIRT6 expression occurs in cases of Multiple Myeloma (MM) and some solid tumors, and in some instances is associated with poor clinical outcome [47-52]. Thus, SIRT6 could have oncogenic rather than tumor suppressive functions in certain contexts.…”
Section: Mechanisms Of Tumor Suppression and Regulation Of Cancer Promentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT6 copy number is increased in some hematopoietic cancer cell lines [5]. Moreover, elevated SIRT6 expression occurs in cases of Multiple Myeloma (MM) and some solid tumors, and in some instances is associated with poor clinical outcome [47-52]. Thus, SIRT6 could have oncogenic rather than tumor suppressive functions in certain contexts.…”
Section: Mechanisms Of Tumor Suppression and Regulation Of Cancer Promentioning
confidence: 99%
“…Alternatively, SIRT6 overexpression in these cancers could represent a compensatory mechanism to oppose tumor progression. Indeed, increased SIRT6 expression in MM cells inhibits tumor cell proliferation via H3K9 deacetylation and transcriptional repression of pro-proliferative MAPK/ERK target genes, and enhances SIRT6-dependent DNA damage response functions (See Figure 3d-e, Box 2) [47]. These findings suggest that modulation of SIRT6 activity in cancer cells varies with tumor type and cancer stage, and elucidating the complex mechanisms and pleiotropic effects of SIRT6 in cancer cell biology will be crucial for attempts to target SIRT6 for cancer therapy.…”
Section: Mechanisms Of Tumor Suppression and Regulation Of Cancer Promentioning
confidence: 99%
“…Some HDACs are upregulated in colorectal, stomach, oesophagus, breast, ovary, lung, pancreas, thyroid, prostate, melanoma, neuroblastoma and oral cancers (528), while some SIRTs are upregulated in myeloma, breast, liver and thyroid cancers (2932). Downregulation of HDAC4 in glioblastoma (33), SIRT1 and SIRT6 in colorectal cancer (34,35) and SIRT6 in pancreas cancer (35) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In multiple myeloma (MM), SIRT6 is highly expressed as adaptive response to genomic stability, and its overexpression is associated to proliferation and poor prognosis. 22 Cea et al 22 demonstrated in vitro and in a human MM xenograft model that SIRT6 down-regulates the expression of ERK signaling-related genes and suppresses the activity of ETS-domain transcription factor (ELK1), increasing DNA repair level via Chk1 (a critical messenger of the genome integrity checkpoints involved in the evolution of human cancer 23 ), and conferring resistance to DNA-damaging agents. In this scenario, the paper by Cagnetta et al 24 studies the biological relevance and the genomic instability and poor prognosis associated with the mRNA upregulation of SIRT6 in the acute myeloid leukemia (AML) cells compared with low SIRT6 levels detected in normal CD34 + hematopoietic progenitors.…”
Section: Sirt6 As a Tumor Promotermentioning
confidence: 99%